2022
DOI: 10.1073/pnas.2204752119
|View full text |Cite
|
Sign up to set email alerts
|

TPL2 kinase expression is regulated by the p38γ/p38δ-dependent association of aconitase-1 with TPL2 mRNA

Abstract: p38γ and p38δ (p38γ/p38δ) regulate inflammation, in part by controlling tumor progression locus 2 (TPL2) expression in myeloid cells. Here, we demonstrate that TPL2 protein levels are dramatically reduced in p38γ/p38δ-deficient (p38γ/δ −/− ) cells and tissues without affecting TPL2 messenger ribonucleic acid (mRNA) expression. We show that p38γ/p38δ posttranscriptionally regulates the TPL2 amount at two different levels. p38γ/p38δ interacts with the TPL2/A20 Bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Since p38γ expression in p38γ/δKO cells restores TPL2 levels independently of its kinase activity ( Risco et al, 2012 ; Escós et al, 2022 ), we decided to generate a p38γ/δKIKO mouse line by crossing Mapk12 D171A/D171A and Mapk13 −/− mice. p38γ/δKIKO mice, which have catalytically inactive p38γ and lack p38δ, will not have either p38γ or p38δ kinase activity, as p38γ/δKO mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since p38γ expression in p38γ/δKO cells restores TPL2 levels independently of its kinase activity ( Risco et al, 2012 ; Escós et al, 2022 ), we decided to generate a p38γ/δKIKO mouse line by crossing Mapk12 D171A/D171A and Mapk13 −/− mice. p38γ/δKIKO mice, which have catalytically inactive p38γ and lack p38δ, will not have either p38γ or p38δ kinase activity, as p38γ/δKO mice.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that TPL2 protein levels, and therefore activation of the ERK1/2 pathway by TLR4, were regulated by p38γ independently of its kinase activity. Accordingly, we have recently demonstrated that p38γ, and also p38δ, kinase-independent activity regulates the amount of TPL2 protein at two posttranscriptional levels: (1) increasing TPL2 protein stability by binding to the complex TPL2/ABIN2/Nuclear Factor-κB1p105 (NF-κB1p105), and (2) modulating Map3k8 mRNA translation ( Escós et al, 2022 ). The RNA binding protein aconitase-1 (ACO1) interacts with the 3′ untranslated region (UTR) of Map3k8 mRNA, repressing its translation and decreasing the levels of TPL2 protein in the cells ( Escós et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the specific roles and molecular mechanisms of these kinases in the innate immune responses have not been fully characterized. Recent studies have shown that p38γ/p38δ control the levels of Tumour Progression locus 2 (TPL2), the key MAP3K upstream of ERK1/2 in myeloid cells, by regulating TPL2 mRNA translation ( Escós et al, 2022 ). This is a mechanism by which p38γ/p38δ modulate innate immune responses, since the activation of the TPL2-ERK1/2 pathway is involved in the production of several key cytokines, including Tumour Necrosis Factor α (TNFα) and Interleukin-1β (IL-1β), in response to TLR activation ( Risco et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The production of cytokines and chemokines triggered by C-type lectin receptor (Dectin-1) and Toll like receptor (TLR) stimulation is reduced in macrophages lacking p38γ/p38δ (Alsina-Beauchamp et al ., 2018). Also, compound p38γ/p38δ deficiency substantially reduces TPL2 mRNA translation and TPL2 protein levels in macrophages (Risco et al ., 2012; Alsina-Beauchamp et al ., 2018; Escos et al ., 2022). TPL2 is the key MAP3-kinase upstream of the MKK1-ERK1/2 in myeloid cells in innate immune responses.…”
Section: Introductionmentioning
confidence: 99%